Karya Lukis Evelyna Dianita Dalam Kajian Sosiologi Historis - Dian Sari, Nani; Justian, Repi; Dehadi, Mickhella (Besaung : Jurnal Seni Desain dan Budaya, 2024)
Modern Indonesian painting developed in several big cities such as Yogyakarta, Bandung, Bali and also spread to other areas such as Bukittinggi and Padang. The art of painting in West Sumatra was pioneered by two great figures in the art of painting, namely Wakidi and M. Syafei. From the role of Wakidi and M. Syafei, several artists were born who are active at both regional and national levels, such as Ipe Makruf, Usman Efendi, Arby Samah, Afianto Arifin, Kamal Guci and others. Since then, young artists, both male and female, have emerged. One of the female painters from West Sumatra who is productive in painting is Evelyna Dianita, who is the daughter of the painter Afianto Arifin. Evelyna Dianita is a female painter born in Bukittinggi on 13 July 1966. In her artistic journey, Evelyna Dianita has participated in many well-known exhibition events, both solo and group. Most of his works are inspired by the works of his father "Afianto Arifin" with a naturalist painting style, only he emphasizes female figures more. The method used is the historical research method, which is a problem solving procedure using legacy data, both to understand events or conditions that occurred in the past, regardless of the current situation in relation to past events or conditions. Keywords : Evelyna Dianita, Painting, female painting artist